Design and construction of a precision tubular linear motor and controller - Kim, Won-jong; Howze, Jo W.; Lee, Sooyong (Texas A&M University, 2004)
A design for a novel tubular high-precision direct-drive brushless linear motor has been developed. The novelty of the design lies in the orientation of the magnets in the mover. In conventional linear motors the magnets of the armature are arranged such that the attractive poles are adjacent throughout, in an NS-NS-NS orientation, where N denotes the north pole and S denotes the south pole of the magnet. In the new design, the magnets in the moving part are oriented in an NS-NS-SN-SN orientation. This change in orientation yields greater magnetic field intensity near the like-pole region. The magnets of the mover are encased within a brass tube, which slides through a three-phase array of current-carrying coils. As the coils are powered, they induce a force on the permanent magnets according to the Lorentz force equation. The primary advantages of the motor are its compact nature, fast, precise positioning due to its low-mass moving part, direct actuation, extended travel range, and ability to extend beyond its base. The linear motor is used in conjunction with a position sensor, power amplifiers, and a controller to form a complete solution for positioning and actuation requirements. Controllers were developed for two applications, with a lead-lag as the backbone of each. For the first application, the principal requirements are for fast rise and settling times. For the second application, the primary requirement is for near-zero overshoot. With the controller for application 1, the motor has a rise time of 55 ms, a settling time of 600 ms, and 65% overshoot. With the controller for application 2 implemented, the motor has a rise time of 1 s, a settling time of 2.5 s, and 0.2% overshoot. The maximum force capability of the motor is measured to be 26.4 N. The positioning resolution is 35 ?m. This thesis discusses the motor's physical design, construction, implementation, testing, and tuning. It includes specifications of the components of the motor and other necessary equipment, desired and actual motor performance, and the primary limitations on the precision of the system.